2013
DOI: 10.1371/journal.pgen.1003465
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Requirements for Signaling from an Autoactive Plant NB-LRR Intracellular Innate Immune Receptor

Abstract: Plants react to pathogen attack via recognition of, and response to, pathogen-specific molecules at the cell surface and inside the cell. Pathogen effectors (virulence factors) are monitored by intracellular nucleotide-binding leucine-rich repeat (NB-LRR) sensor proteins in plants and mammals. Here, we study the genetic requirements for defense responses of an autoactive mutant of ADR1-L2, an Arabidopsis coiled-coil (CC)-NB-LRR protein. ADR1-L2 functions upstream of salicylic acid (SA) accumulation in several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
129
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(138 citation statements)
references
References 59 publications
7
129
0
Order By: Relevance
“…5a,b). Similar to a previous report (Roberts et al, 2013), we observed that individual adr1, adr1-L1 and adr1-L2 knock-out mutants affect lsd1-2 phenotypes Among the three ADR genes, ADR1-L1 and ADR1-L2 are expressed at higher levels, whereas ADR1 is expressed at a lower level ( Fig. S6; Roberts et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…5a,b). Similar to a previous report (Roberts et al, 2013), we observed that individual adr1, adr1-L1 and adr1-L2 knock-out mutants affect lsd1-2 phenotypes Among the three ADR genes, ADR1-L1 and ADR1-L2 are expressed at higher levels, whereas ADR1 is expressed at a lower level ( Fig. S6; Roberts et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…53,54 Signaling gradients that establish cell death control borders at sites of pathogen recognition have been demonstrated in plants. 48,[55][56][57][58] Importantly, the studies that reported a pro-survival role of autophagy during pathogentriggered HR cell death used relatively old plants. 8,51,52 With age, autophagy mutants become prematurely senescent and accumulate high levels of ROS that can drive accumulation of SA, potentially increasing their vulnerability to ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…These functions include promoting SA-mediated basal resistance, a low-level postinfection response that impedes the growth of virulent pathogens, and SAR (Falk et al, 1999;Wiermer et al, 2005;Truman et al, 2007;Vlot et al, 2009;Rietz et al, 2011). Additionally, EDS1 regulates SA-independent defense signaling in one or more pathways acting redundantly with SA (Bartsch et al, 2006;Venugopal et al, 2009;Roberts et al, 2013). FMO1, for example, acts upstream of SA in systemic uninfected tissues (Mishina and Zeier, 2006;Shah and Zeier, 2013) and is associated with EDS1-dependent local responses that are genetically separable from SA (Bartsch et al, 2006).…”
mentioning
confidence: 99%